(3GdEeGeI hGdSjGSIs - (3YHO Gddg Hf eSde Hf bJjHI GdOjnfnhQqj, CHh eMeO, GHf obnJrjnHI, J (B276 (3g` s
(3ChdgG (B:s
(3faJM cdGefG HMeO Gddg hfahS fGOjfG HPcQg hGdKfGA Ydjg CdN bd CffG CSO GHf ehSi bGd s
(3BNQgG (B:s
(3afgV GdbUQ aONdg aCNP CNGg hKGbg hMHSg hCTGQ Edi Ceg CYGfJg Ydjg , agQH eMeO ef Hjf jOjg , aHYK ai WdHg aCNP hbJd JeJ GdSjGSI hGdEeGeI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B137s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B122 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B31 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs